DNA-chart visual tool for topological higher order information from spatio-temporal trajectory dataset. (15th October 2018) - Wang, Ye; Lee, Kyungmi; Lee, Ickjai
Highlights: A framework for topological HOI visualisation using higher order Voronoi diagrams. A novel DNA-chart approach for topological HOI visualisation. Topological HOI impact factor for topological relationship measurement. Areal visualisation of the same topological HOI. Flicker case study demonstrating the applicability of proposed methods. Abstract: With increasing amount of trajectory dataset being generated and collected, trajectory data has become a ubiquitous type of data important in many different application domains. Research challenges faced are to analyse and retrieve useful higher order information from trajectory datasets to deal with dynamic and "what-if" complex decision making problems. In this paper, we propose a new visualisation approach and quantitative metrics to model and analyse topological higher order information from trajectory datasets. The proposed higher order DNA chart can help decision makers to compare different topological higher order information from different trajectories. We also define higher order trajectory area that models a geometrical area representing the same higher order information. We introduce a higher order DNA impact factor that defines top- k higher order information, and the relationship between trajectory datasets and points-of-interest. A case study using trajectory data extracted from Flickr illustrates the applicability and usefulness of these proposed visual tools and metrics.